O geoprocessamento como ferramenta metodológica ao monitoramento ambiental - Costa, Daniella Tancredo de Matos Alves (2003)
This proposal presents a study that establishes a model of ambient all diagnosis about the aquatic part of Sepetiba's bay, counting on the Geoprocessing's technical support. It is understood here, as geoprocessing mechanisms, the set of techniques that characterize for using the distributed data within a geographical frame of reference. Therefore, interactions between the Remote Sensing in Orbital base, the Computerized Cartography, the Environmental Statistics through the use of Numerical Models of Land (MNT) and the use of Systems of Geographic Information - SIGs are considered in this work. The methodology used had associated field trips to make possible the understanding of the ground truth, as well as, to register the representative information about the use of the land of basin of Sepetiba. The points of samples are distributed in way a to composed a pattern representative of the main contracting parties of the bay, attending, in this way, to a geoambiental perspective. The primary data used here consists of the work developed by Fundação Estadual de Engenharia do Meio Ambiente - FEEMA, for the basin of Sepetiba, and divulged by the Coastal Management Project of Rio de Janeiro. In cabinet, it was given emphasis to geoprocessing work, where it had been elaborated, with cartograhic support, thematic mappings that characterize the space distributions of heavy metals Cadmium, Chromium, Lead, Iron, Manganese,Nickel and Zinc. The data are related to the 16 points shown, considering times of drought and rain.There are also representative thematic maps about the Temperature, Dissolved Oxygen and Salinity variation consist, characterizing different depths Sepetiba's bay. To understand the case of the ambient diagnosis of the Bay it is presented, from images of satellite LANDSAT digital TM-5, digital processing for the characterization of the pens of sediment in the aquatic part and the diagnose of the land use in the great basin of Sepetiba. The math of the different thematic maps, through the use of a Geographical Systems Informations - GSI, allowed the technical definition of the areas that present greaters and minors negative effects in water ground of the bay. The final product of this proposal takes care of the possibility of establishing a model for the monitoring of Sepetiba's bay supported the geoprocessing's technology. This model can be possibly offered to institutions and technical support companies, that deal with environmental issues on the coastal ecosytems. This perspective will be able to attend evaluation and control studies about the environmental impacts in bay areas, as well as, in lagoons and coves.